What is the COVID-19 Risk Zone Colours Impact: Health Related-Quality of Life of Indonesian Healthcare Workers - Handayani, Nur Septia; Putri, Berliana Devianti; Ramdan, Iwan Muhamad (Universitas Airlangga, 2025)
Introduction: In Indonesia, over 1000 healthcare workers have died due to COVID-19. Healthcare workers face increased workloads and negative perceptions, including discrimination and verbal or physical violence, which may impact their quality of life. Health-related quality of life encompasses both physical (PCS) and mental (MCS) health components. This study aims to analyze the health-related quality of life of healthcare workers who are obliged to service during the COVID-19 pandemic in Indonesia and occupational health and safety factors based on the workplace location risk zone. Methods: A cross-sectional online survey was conducted involving 149 healthcare workers from several areas of Indonesia as representatives from the red and orange risk zones. Health-related quality of life was measured using the SF-36 questionnaire. Differences in health-related quality of life scores were analyzed using Mann-Whitney test base on COVID-19 risk Zone and PPE availability. Results: Healthcare workers in the lower-risk (orange zone) exhibited better mental health scores (MCS 75±15.5) compared to those in the high-risk zone (red zone) (MCS 66.2±15.2). Additionally, those who received a complete set of PPE from their workplace had better health-related quality of life scores workplace (MCS 76.9±14.2, PCS 77±16) than those who lacked such provision (MCS 73±17.6, PCS 82±13.4). Furthermore, healthcare workers with access to PCR testing at their workplace tended to have higher quality of life scores than those who only had access to rapid testing. Conclusion: These findings highlight how the Health System addresses the pandemic, particularly regarding the health and safety of healthcare workers